Fluorine‐Containing Drugs Approved by the FDA in 2018. Issue 51 (8th July 2019) - Mei, Haibo; Han, Jianlin; Fustero, Santos; Medio‐Simon, Mercedes; Sedgwick, Daniel M.; Santi, Claudio; Ruzziconi, Renzo; Soloshonok, Vadim A.
Abstract: Over the last two decades, fluorine substitution has become one of the essential structural traits in modern pharmaceuticals. Thus, about half of the most successful drugs (blockbuster drugs) contain fluorine atoms. In this review, we profile 17 fluorine‐containing drugs approved by the food and drug administration (FDA) in 2018. The newly approved pharmaceuticals feature several types of aromatic F and CF3, as well as aliphatic (CF2 ) substitution, offering advances in the treatment of various diseases, including cancer, HIV, malarial and smallpox infections. Abstract : Fluorinated drugs : This Review outlines 17 fluorine‐containing drugs approved by the food and drug administration (FDA) in 2018. These newly developed fluorinated pharmaceuticals are recommended for the treatment of various diseases, including cancer, HIV, malarial and smallpox infections.